Central Obesity and BMI Associated with Different Phenotypes of Polycystic Ovary Syndrome in Adolescent - Bahar Morshed Behbahani; Marzieh Akbaezadeh (Intelektual Pustaka Media Utama, 2017)
Adipose tissue distribution is effective in metabolic complications resulting from obesity. Fat accumulation in the body, particularly increase in visceral fat, is a major risk factor of diabetes and cardiovascular diseases. The present study aimed to determine the prevalence of obesity and android obesity based on various phenotypes of Polycystic Ovarian Syndrome (PCOS) in 14-18 year old high-school girl students in Shiraz in 2009. This descriptive study was conducted on 14-18 year old high-school girl students in Shiraz in 2009. Considering the confidence coefficient of 95% and loss rate of 20%, a 3190subject sample size was determined for the study. The participants were selected through purposive sampling. After obtaining written informed consents, demographic information questionnaire was completed and the participants were examined regarding hirsutism, acne, alopecia, and menstrual disorders. Besides, the criteria proposed by Adams et al. were employed to diagnose PCOS in sonography. Android obesity and Body Mass Index (BMI) were evaluated, as well. The results of independent t-test showed no significant difference among various phenotypes of PCOS regarding mean android obesity and BMI (P>0.05). The results of the present study revealed no significant relationship between girl adolescents' obesity and various phenotypes of PCOS. However, adolescents should be informed about the long-term hyperandrogenic outcomes which are accompanied by insulin secretion and endanger their health after the age of 40 years.